Auditing employee ownership in a neo-liberal world - Knyght, P. R.; Kouzmin, Alexander; Kakabadse, Nada K.; Kakabadse, Andrew P. (Emerald Group Publishing Limited, 2010)
Purpose - Employee ownership has attracted much attention across the globe. Whether affected by the global financial crisis (GFC), or not, this paper seeks to canvass what is known about employee ownership in neo-liberal political economies. Design/methodology/approach - This paper is a literature review, cross cultural analysis and critique. Findings - The findings indicate future research directions. Research limitations/implications - The paper suggests a reconsideration of organizational configurations for possible greater application in the future. Social implications - The paper hightlights the re- regulation of neo-liberal markets. Originality/value - The paper focuses on employee share ownership schemes.